Achieving Motor Development Milestones at the Age of Three Months May Determine, but Does Not Guarantee, Proper Further Development. (9th December 2013) - Gajewska, Ewa; Sobieska, Magdalena; Kaczmarek, Elżbieta; Suwalska, Aleksandra; Steinborn, Barbara
Abstract : Proper motor performance at 3rd month is necessary for further motor development. The paper aims to demonstrate the reliability, sensitivity, and predictive value of an original motor performance assessment tool in comparison with the neurological assessment at 3, 6, and 9 months. Children (n = 123 ), born at term without pre- or perinatal complications, born at term with pre- or perinatal complications, or born preterm, were assessed at the age of 3, 6, and 9 months, by a neurologist and a physiotherapist. The physiotherapist evaluated 15 qualitative features typical for the age of 3 months in the prone and supine positions. The final neurological assessment determined the degree of developmental disorder. Neurological and global physiotherapeutic assessments showed a statistically significant correlation. Qualitative assessment results were very good in healthy children and decreased with worsening neurological diagnoses. Children diagnosed with cerebral palsy did not show proper qualitative features of 3 months when analyzed at 3, 6, and 9 months. Children with delayed motor development revealed minor qualitative performance impairments as early as 3 months but improved with age. Qualitative assessment at 3 months not only facilitates diagnosis of major developmental disorders but is also a good predictor of delayed motor development in children.